2019
DOI: 10.1108/jamr-08-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the characteristics of a high-performance finance function

Abstract: Purpose The concept of the high-performance organization (HPO) receives much attention nowadays. To create and sustain an HPO, all parts of the organization must contribute, especially the finance function, whose relations with every part of the organization mean that it can be regarded as the spider in the organizational web. The paper aims to discuss this issue. Design/methodology/approach This study develops the high-performance finance function (HPFF) framework based on the HPO framework, a scientificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…In this context, the term 'finance function' refers to all the financial processes of an organization. The professionals responsible for financial processes usually work in the finance department, but can also operate in other parts of the organization, for instance as business unit controllers (de Waal et al, 2019). Closer examination reveals that such studies mainly concern creating a world-class finance function (O'Connor et al, 2014(O'Connor et al, , 2015 or a high performing finance function (CFO Research, 2014;de Waal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, the term 'finance function' refers to all the financial processes of an organization. The professionals responsible for financial processes usually work in the finance department, but can also operate in other parts of the organization, for instance as business unit controllers (de Waal et al, 2019). Closer examination reveals that such studies mainly concern creating a world-class finance function (O'Connor et al, 2014(O'Connor et al, , 2015 or a high performing finance function (CFO Research, 2014;de Waal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The professionals responsible for financial processes usually work in the finance department, but can also operate in other parts of the organization, for instance as business unit controllers (de Waal et al, 2019). Closer examination reveals that such studies mainly concern creating a world-class finance function (O'Connor et al, 2014(O'Connor et al, , 2015 or a high performing finance function (CFO Research, 2014;de Waal et al, 2019). Very little literature can be found that discusses making the finance function 'future-ready' so that it can deal with changes in its environment, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations